Assessment in education: Current trends, problems and contradictions (review of scientific publications) - I. B. Shmigirilova; A. S. Rvanova; O. V. Grigorenko (Образование и наука)
Introduction. Modern views on the goals and content of education around the world are changing the viewpoints on educational assessment: the goals and functions of assessment are expanded, new assessment forms and tools are being introduced, the roles of students and teachers in assessment practice are revised. Global trends in educational assessment are reflected in national education systems, many of which have made the transition to criteria-based assessment. This process is accompanied by a rapid increase in the volume of scientific and methodological publications on this issue, reducing the ability of scientists and practising educators to comprehend the cumulative evidence in this area of research, which is important at the stage of reform. The solution to this problem can be facilitated by an analytical review of sources, representing a generalisation of international experience in the development of educational assessment.Aim. Based on the analysis of scientific publications, the current research is aimed to comprehend and generalise the current trends prevailing in the world theory and practice of assessment of student learning outcomes, to identify problems and contradictions as a potential basis for the occurrence of risks in assessment practices, to determine the current research directions towards the improvement of assessment in education.Methodology and research methods. The scientific papers of the last thirty years, revealing the issues of the education process assessment, have been used in the research. Sources were selected through the methods of descriptive and bibliometric analysis. The comparative and aspect-based analyses were employed in the research.Results. The wide range of assessment goals confirms the significance of the assessment as the education component; however, it results in some contradictions between the goals, which appear in estimated dichotomies: formative and summative assessment, norm-based and criteria-based assessment. Despite the contrapositive between the formative and summa-tive assessments, the analysis conducted shows the necessity of their integration. The variety of theoretical approaches to the interpretation of assessment forms, the ambiguous definition and use of terminology, the multiplicity of criteria-based assessment models, qualitatively different approaches to the development of criteria and the creation of assessment rubrics on their basis are sources of risks in the practice of educational assessment. In addition, an obstacle to ensuring effective assessment of students’ educational achievements is the insufficient level of competence of teachers as assessors, the unpreparedness of students themselves to take responsibility for the results of their learning.Scientific novelty. From a critical standpoint, the ideas are presented and the results of discussions on the problems of assessing the educational results of students in scientific sources are summarised. The analysis performed can serve as a basis for further research to build an ordered theoretical framework for assessment in education.Practical significance. An analysis of the pros and cons of international experience in the field of educational assessment can help scientists and practising teachers gain a more objective view of new approaches to the assessment of student learning outcomes, thereby contributing to the minimisation of the manifestation of possible risks in the development of assessment tools and procedures and their implementation in educational practice.